Marketing Margin Analysis of Pork Retailers in Airmadidi Market - Oroh, Franky N.S (Jambura Journal of Animal Science, 2024)
This research aims to determine the form of channels, marketing margins and profits, as well as the share of prices received by pork producers at the Airmadidi Market. The research used a survey method for producers, retailers and final consumers. The sample was determined using a purposive sampling technique, namely a sample selection technique with certain considerations in accordance with the research objectives, based on the consideration that the retailers sampled were regular retailers, who sell at the market every day. ..The research results show that there are two forms of marketing channels for pig marketing at the Airmadidi market, namely direct and indirect. The average selling price of pork at the producer level is IDR 32,000/kg, while the price at the final consumer level is IDR 70,000/kg carcass weight. Then the marketing marginattheretailerlevelisIDR38,000,thus the portion received by the trader retailers by 46%. Revenue at the retailer level is IDR. 29,503,222 with total marketing costs of IDR 18,237,700, resulting in a profit received at the retailer level of IDR 11,265,522 per retailer.